Perlindungan Hukum Terhadap Perusahaan Nasional Dalam Transaksi Bisnis Internasional Tanpa Perjanjian Tertulis - Rina Shahriyani Shahrullah; Wagiman Wagiman; Lindasari Novianti (Fakultas Hukum, Universitas Internasional Batam, 2015)
This research examines the judicial review of the activities of international business transactions without a written agreementcontract, which is conducted by one of the freight forwarding company, PT. Kundur Prima Karya domiciled in Batam. The researchis aimed to analyze and discover problems faced, to analyze the legal protection that can be applied, to provide the best solutions in international business transactions without a written contract.The method used in this research is sociological (empirical), descriptive in the explanation and is aimed to provide, to obtain an overview of the implementation of international business transactions in the field of freight forwarding with clients from Singapore. Data collection is done by collecting evidence from corporate documents.The research results showed some problems and constraints faced by the company with the clients domiciled in Singapore on the difficulties of collecting debts, the debts were not paid, there were no legal powers that could ensnare the clients who caused these matters of receivables, as there was no written agreement contract. The law protection which ought to be obtained, though we refer to the Article 1320 of the Civil Code, and International Private Law, this matteris still unable to be resolved properly, as it can be observed that there was no written agreement contract in the case of business transactions and cooperations made. The law chosen (choice of law) Singapore Laws, and a choice of forum lawsuit was filed in the Court of Singapore where the client concerned resides.